(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The wireless technology is developing having rapid speed with advanced techniques. It is an emerging technology in various fields of communication like internet access, location-based services, mobile entertainment services, mobile financial services and video conferencing system etc. The users may use such applications at anytime and anywhere via mobile communication